Análise da viabilidade econômica do policultivo de Jundiás, Carpas e Tilápias-do-Nilo como uma alternativa de modelo de cultivo de peixes na piscicultura familiar da pequena propriedade - Ritter, Filipe (2011)
With a growing world population and increasing demand for quality food in sufficient quantities, aquaculture fits in this context as active producer of high quality animal protein in large quantities by field use. The production of fish in farm ponds and has practiced for over five decades in Rio Grande do Sul, and the system is commonly used in carp polyculture, which consists of intercropping different species of carp to improve the performance of each one and therefore achieve greater productivity. But the carp polyculture currently used has a low technological level, the production obtained is considered small and, moreover, is the release of water in the eutrophic water bodies natural d causing an imbalance in the natural aquatic environment. Studies have been performed by adding the silver catfish, the traditional polyculture, thus obtaining good results. Some studies were performed on economic viability, but with a single species, or consortium, as is the case of polyculture of shrimp and Nile tilapia. We tested the polyculture with partial subtituição 25, 50 and 75% of silver catfish and carp by Nile tilapia. We analyzed the economic viability of all polycultures studied under the condition of certainty by obtaining the Net Present Value (NPV), Annual Value (AV), Internal Rate of Return (IRR) and Pay Back. In conditions of uncertainty held on sensitivity analysis and evaluation through the Monte Carlo method. It was concluded that replacing 25% of silver catfish and carp by Nile tilapia has higher biomass production, parameters of effluent quality, and that an investment in polyculture with vita useful 25 years is economically feasible for a fee Minimum Attractiveness (TMA) of 6.17%.